Determinan Enterpreneurial Motivation Mahasiswa Perbankan Syariah - Siswanto, Siswanto Siswanto (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2016)
This study was conducted to explore factors motivating students to be enterpreneur. Factor analysis approach used to attain the objective. The analysis used four stages. Namely; choose a variable, variable extraction, rotation and indentified variables. Total sample of the researsh were 100 respondents. The results showed some biographical characteristics which included characteristics based on age, gender, enterpreneurial intentions, type of business, opinions and backrounds. Based on the results, there were six important factors which motivated students to be enterpreneur, namely; need for achievement, locus of control, external environment, self efficacy, material encouragement and independence.